2021
DOI: 10.3390/cells10092501
|View full text |Cite
|
Sign up to set email alerts
|

Are Interactions between Epicardial Adipose Tissue, Cardiac Fibroblasts and Cardiac Myocytes Instrumental in Atrial Fibrosis and Atrial Fibrillation?

Abstract: Atrial fibrillation is very common among the elderly and/or obese. While myocardial fibrosis is associated with atrial fibrillation, the exact mechanisms within atrial myocytes and surrounding non-myocytes are not fully understood. This review considers the potential roles of myocardial fibroblasts and myofibroblasts in fibrosis and modulating myocyte electrophysiology through electrotonic interactions. Coupling with (myo)fibroblasts in vitro and in silico prolonged myocyte action potential duration and caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 131 publications
(247 reference statements)
0
29
0
2
Order By: Relevance
“…One master switch linking adiposity, thrombosis and pro-arrhythmic atrial remodeling is inflammation. Particularly inflammatory and metabolic remodeling of the epicardial fat depot and its inter-organ communication with the atrial myocardium and blood compartment is increasingly considered to govern obesity-driven AF and thrombosis [13] , [14] . DOAC interfere in this self-perpetuating cross-talk to suppressing obesity-driven inflammatory sequelae and reducing atrial fibrosis and electrical remodeling in various experimental models (reviewed in [15] ).…”
Section: Introductionmentioning
confidence: 99%
“…One master switch linking adiposity, thrombosis and pro-arrhythmic atrial remodeling is inflammation. Particularly inflammatory and metabolic remodeling of the epicardial fat depot and its inter-organ communication with the atrial myocardium and blood compartment is increasingly considered to govern obesity-driven AF and thrombosis [13] , [14] . DOAC interfere in this self-perpetuating cross-talk to suppressing obesity-driven inflammatory sequelae and reducing atrial fibrosis and electrical remodeling in various experimental models (reviewed in [15] ).…”
Section: Introductionmentioning
confidence: 99%
“…The extent and status of EAT have also been shown to be positively correlated with AF [ 45 , 46 ]. Krishnan et al [ 47 ] reported that the adipokines secreted by adipocytes stimulate myofibroblast differentiation in association with the generation of reactive oxygen species, causing pronounced fibrosis in the EAT and myocardium. In addition, adipose tissue influences cardiomyocyte electrophysiology through adipokines.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these two layers of fatty tissue, anatomical data from many histological species indicate that fatty infiltrate is also present at the level of the myocardium, although the fat distribution in the atrial and ventricular myocardium is extremely diverse. In particular, atrial appendages have fat deposits, particularly around the left posterior atrium [ 8 ]. Whereas such fat distributions are deemed normal, fatty infiltration is considered arrhythmogenic, and a variety of pathological cardiac disorders are associated with increased myocardial fat deposits, particularly in the epicardium [ 9 ].…”
Section: Anatomymentioning
confidence: 99%